Increasing EFL Students’ Writing Abilities Using Peer Response Activities via Facebook - M. Zaini Miftah (Indonesian EFL Journal: Journal of ELT, Linguistics, and Literature, 2016)
This study was aimed to increase EFL students’ abilities in writing argumentative essay via Facebook by developing peer response activities. The classroom action research was employed in cyclic activities. The subjects were 25 Indonesian fourth-year undergraduate EFL students who enrolled in Writing III course. The data were gained from writing task, observation, and field notes. The result shows that this strategy with the appropriate instructional procedures can increase the EFL students’ abilities in writing argumentative essay. It is indicated by the increases of the students’ writing achievement and involvement in writing class during peer response activities via Facebook. Hence, it gives insights to employ this way as an alternative teaching technique in writing classroom because of its effectiveness.